2022
DOI: 10.1177/10732748211072983
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Cancer Screening Rates Among Uninsured Patients in Free Clinics: A Retrospective Cohort Study of Cancer Survivors and Non-cancer Survivors

Abstract: Background There is limited research on screening rates among uninsured cancer survivors. Uninsured cancer survivors are at higher risk of poorer health outcomes than the insured due to limited access to preventative screening for secondary cancers. This study examines the rates of surveillance and screening of uninsured cancer survivors and compares to uninsured patients without a cancer history seen in free clinics. Methods Data were collected retrospectively from electronic medical records and paper charts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In addition, limited time and workload pressure among providers may be the drivers for lack of communication between patient and provider [ 39 ]. Having insurance coverage to preventive health services for common cancer screening may also explain access to CRC screening [ 35 , 43 ], which is consistent with our finding that having insurance was associated with CRC screening uptake. Therefore, patient-physician CRC screening communication could become a critical channel for timely CRC screening use among cancer survivors [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, limited time and workload pressure among providers may be the drivers for lack of communication between patient and provider [ 39 ]. Having insurance coverage to preventive health services for common cancer screening may also explain access to CRC screening [ 35 , 43 ], which is consistent with our finding that having insurance was associated with CRC screening uptake. Therefore, patient-physician CRC screening communication could become a critical channel for timely CRC screening use among cancer survivors [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Higher screening use from this study may be due to using registry-based data, which usually have more accurate information compared to self-reported data. Variations of CRC screening utilization across different cancer types may be influenced by doctor’s recommendations on screening tests [ 23 ] and CRC risk perceptions [ 33 , 34 ] as well as insurance coverage to access preventive care [ 32 , 35 ]. Finally, more research on examining CRC screening behaviors in skin and lung cancer survivors are needed due to lack of existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in screening rates among women with breast cancer were comparable to those in the general population during the same period from 2009 to 2016 [9]. Suboptimal cancer screening rates in cancer survivors and disparities in screening uptake in cancer survivors have been raised as problems in the management of secondary cancer prevention in survivorship care plans for cancer survivors [18][19][20][21]. Controversial results regarding cancer screening rates in cancer survivors compared with the general population or people without cancer have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 We found that adjuvant chemoradiotherapy was underutilized in communities with uninsured patients. This particular population faces severe barriers to accessing healthcare since they have low rates of preventive care screenings, 36 are less likely to see doctors for health concerns, 37 and have higher rates of emergency department use compared with insured patients. 38 Disruptions in insurance coverage reduce cancer treatment adherence and overall cancer survival.…”
Section: Discussionmentioning
confidence: 99%